Bioinformatics-Driven Vaccine Design for Trematodes: Advances, Challenges, and Future Directions (Bangladesh Journal of Infectious Diseases, 2025)
Trematodes, or flukes, are parasitic flatworms that cause neglected tropical diseases such as schistosomiasis, fascioliasis, clonorchiasis, opisthorchiasis, and paragonimiasis, affecting millions worldwide and burdening public health and livestock industries. Control currently relies on chemotherapy with drugs such as praziquantel and triclabendazole, but reinfection, emerging resistance, and challenges in sustained elimination underscore the urgent need for vaccines. Vaccine development, however, remains difficult due to the parasites’ complex biology, multi-stage life cycles, and immune evasion strategies. Traditional empirical vaccine approaches have achieved limited success, but bioinformatics now offers transformative opportunities. Immunoinformatics enables systematic mining of genomic and proteomic data, prediction of immune-relevant antigens, cost-effective narrowing of candidates, and even cross-species applications. Key challenges remain, including stage-specific antigen diversity, parasite immune evasion, gaps between in silico predictions and in vivo validation, host genetic variability, and limited resources in endemic regions. Future prospects include integrating multi-omics data, applying artificial intelligence for improved predictions, and advancing novel platforms such as mRNA and nanoparticle vaccines. A One Health strategy targeting both humans and livestock could further enhance impact. Harnessing these approaches may finally enable effective trematode vaccines and sustainably reduce their global disease burden.Bangladesh Journal of Infectious Diseases, June 2025;12(1):174-180